Chromato-mass spectroscopy of tinctures from the underground part of Valerian plants growing in Zaporizhzhia region - Odyntsova, V. M.; Korniievskyi, Yu. I.; Skoryna, D. Yu.; Korniievska, V. H.; Одинцова, Віра Миколаївна; Корнієвський, Юрій Іванович; Скорина, Дмитро Юрійович; Корнієвська, Валентина Григорівна (Запорізький державний медичний університет, 2022)
The aim of the work is to determine the component composition of valerian tinctures made from rhizomes with valerian roots of different species growing in the Zaporizhzhia region by gas chromatography and to carry out their comparative analysis. Materials and methods. Samples of rhizomes with valerian roots made from medicinal plant raw materials of valerian according to the traditional production recipe (Tinctura Rhizomata cum radicibus Valerianae (1:5)) from different species of valerian growing in the Zaporizhzhia region were selected for experimental studies: Valerian stolonifera Czern. – Kantserivska Balka, Zaporizhzhia district, Zaporizhzhia region; V. exaltata Mikan. – Shyroke village, Vasylivskyi district, Zaporizhzhia region; V. tuberosa L. – Khortytsia Island, Zaporizhzhia; V. collina Wallr. – right bank of the Dnieper River, Zaporizhzhia. The component composition of valerian tinctures was studied using an Agilent 7890B gas chromatograph with a mass spectrometric detector 5977B. Results. The component composition of tinctures from the underground part of valerian plants growing in the Zaporizhzhia region was identified and analyzed with chromato-mass spectrometry. Мета роботи – методом газової хроматографії визначити компонентний склад настойок валеріани, виготовлених із кореневищ з коренями валеріани різних видів, які зростають у Запорізькому краї, та здійснити їх порівняльний аналіз. Матеріали та методи. Для експериментальних досліджень обрали зразки настойок кореневищ із коренями валеріани, виготовлені з лікарської рослинної сировини валеріани за традиційною виробничою рецептурою (Tinctura Rhizomata cum radicibus Valerianae (1:5)) із різних видів валеріани, що зростають у Запорізькому краї: Valeriana stolonifera Czern. – Канцерівська балка, Запорізький район Запорізької області; V. exaltata Mikan. – с. Широке, Василівського району Запорізької обл.; V. tuberosa L. – о. Хортиця, м. Запоріжжя; V. collina Wallr. – правий берег р. Дніпро, м. Запоріжжя. Компонентний склад настойок валеріани досліджували за допомогою газового хроматографа Agilent 7890B з мас-спектрометричним детектором 5977B. Результати. За допомогою хромато-мас-спектрометрії ідентифікували та проаналізували компонентний склад настойок із підземної частини рослин роду валеріана, що зростають у Запорізькому краї.
Хромато-мас-спектроскопія настойок із підземної частини рослин роду валеріана, що зростають у Запорізькому краї
Odyntsova V. M. - ORCID ID: 0000-0002-7883-8917; Korniievskyi Yu. I. - ORCID ID: 0000-0001-7863-6736; Skoryna D. Yu. - ORCID ID: 0000-0002-8851-8757; Korniievska V. Н. - ORCID ID: 0000-0001-8307-1282.
Keywords: valerian tincture; gas chromatography; chromato-mass spectroscopy; component composition; quantitative content; настойка валеріани; газова хроматографія; хромато-мас-спектроскопія; компонентний склад; кількісний вміст